The Financial Value of a California Post-Secondary Education - Niendorf, Bruce D.; Beck, Kristine L. (Journal of Accounting and Finance, 2024)
Earning a post-secondary degree involves paying for tuition, fees, books, supplies, and living costs. While in school, students forgo full-time job earnings, and after earning a degree they may have student loans to pay for many years. This study examines 305 California major/school combinations to identify the remaining value after paying the costs of earning a post-secondary degree - the Education Value above and beyond what the average person earns with a high school diploma. We find the best combination delivers an additional $3,713,267 in value across a lifetime, and the least value-added bachelor’s degree combination still delivers $656,100. All combinations are investments in human capital that outperform the long-term average of the U.S. stock market and may be the best investment many people ever make.